Dampak Pengangguran Kemiskinan Dan Konsep Teoritisnya Pada Pandemi Covid-19 - I Ketut Kasna (Universitas Mahendradatta Denpasar, 2020)
Unemployment and poverty are one of the central themes in community and state life. In Indonesia unemployment and poverty have never been the main themes in elections, but there have been quite a number of seminars, public discussions, workshops and launching government programs. According to the Central Bureau of Statistics, total unemployment and poverty in 2019 reached 38,000,686 people (37.70% of the total workforce).Facing poverty unemployment caused by impact pandemic covid-19, governmentcurrently has at least four programs namely Productive Labor Intensive, expanding plantations through inte- grated training, independent business, and TKPMP (Independent Professional Youth Workers). These programs have different orientation and target groups, which reflect the complexity of the problem of unemployment and poverty. However, it seems that these programs have not been implemented comprehensively, so that each program seems to be partial, not related to each oth- er especially with other departmental programs, the problem of poverty, vulnerable groups, and increasing unemployment need to get major attention.These problems also bring negative influences, such as increasingly loosened upsocial ties and weakening of values, and relationships between people. In addition to dealing with various neg- ative impacts of social change that are ignored by the concept of the theory, the phenomenon ex- perienced now is a very basic social cultural change. Information wave accelerationtechnology bring significant changes to poverty reduction which is an impact pandemic covid-19, both at the level of surface structure (attitudes and patterns behavior) and deep structure (value systems, outlook on life, philosophy and beliefs).Changes occur because of cultural contact between the meaning of the dialectics of new values with old values that dominate each other, which allows homoginesis and meoliberalisation in all aspects of life. This condition causes spit and uncertainty in the value of preventionpandemic covid-19 uses more modern values by marginalizing values transcendental. As a result there is a prolonged impact of various forms of moral value distortionreflected in the style, style and lifestyle of people from poverty due to impact pandemic covid-19.